Dendrochirotid holothurians (Echinodermata: Holothuroidea: Dendrochirotida) including four new species, from off Misaki, Japan - Yamana, Yusuke; Kohtsuka, Hisanori (Zootaxa, 2018)
Four new dendrochirotid sea cucumbers, Neocucumis misakiensis sp. nov., Pseudocolochirus misakiensis sp. nov., Lipotrapeza purpurata sp. nov., and Pentamera misakiensis sp. nov., and three other known species, Amphicyclus japonicus Bell, 1884, Cucumaria tegulata Augustin, 1908, and Placothuria ohshimai Liao, 1997, are described from off Jyogashima Island, Misaki peninsula, south coast of Kanagawa Prefecture, Japan. In this study, Cucumaria tegulata Augustin, 1908, is referred to the genus Hemiocnus Mjobo & Thandar, 2016. Furthermore, a new phyllophorid genus Pseudoplacothuria is here erected to accommodate Placothuria ohshimai Liao, 1997. Although its external and internal body morphology and most of the ossicle morphology resemble those of Pentamera spp., it differs in possessing thick lens-shaped ossicles in the body wall, and also in possessing needle-shaped ossicles in the gonadal tubules.